Environmental wisdom messages in javanese proverbs and etymologies: An ecolinguistic study - Shevia Dwi Ningrum (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study aims to describe the flora and fauna vocabulary in Javanese proverbs, environmental messages contained in Javanese proverbs, an ecolinguistic perspective that explains the relationship between language, humans, and nature, and messages of local wisdom contained in Javanese proverbs. Thirteen pieces of data were obtained. Methods: The data were collected using a descriptive qualitative method with note-taking techniques as the data collection method. The research data sources were obtained from written sources in the form of Javanese proverb ebooks. The presentation of the results of the data analysis was carried out using informal techniques conveyed in simple words. Findings: The results of the study show the presence of flora vocabulary in Javanese proverbs, namely katewel, bayem, tebu, lempuyang, and pari. While fauna vocabulary such as bebek, macan, semut, tekek, ula, iwak, gajah, kebo. Conclusion: In addition, Javanese proverbs have environmental messages; the relationship between language, humans, and nature based on an ecolinguistic perspective; and contain messages of local wisdom that describe cultural values, moral messages, views on life, and the importance of maintaining the balance of nature. Novelty/Originality of this article: This study offers a fresh perspective by applying an ecolinguistic approach to specific Javanese proverbs related to flora and fauna, successfully revealing traditional expressions that convey messages of environmental conservation and ecological wisdom alongside cultural moral values.